Hematological parameters abnormalities and associated factors in HIV-positive adults before and after highly active antiretroviral treatment in Goba Referral Hospital, southeast Ethiopia: A cross-sectional study - Negesso Duguma (SAGE Open Medicine, 2021)
Objectives: Hematological abnormalities of the major blood cell lines are frequently reported in patients with HIV-1 infection, in patients without antiretroviral therapy, and during the advanced stages of the disease. Chronic immune activation and inflammation results in the progressive depletion of CD4+ T-cells play a significant role in the clinical progression and pathogenesis of this infection. This study was aimed at assessing the prevalence of hematological abnormalities and their associated factors before and after the initiation of antiretroviral therapy in adults with HIV-1 infection in a referral hospital. Methods: The study was conducted from 1 April to 30 June 2018, at Goba Referral Hospital. A total of 308 HIV-positive adults on treatment were enrolled during the study period. Socio-demographic and clinical data were collected using a structured questionnaire, with pre-highly active antiretroviral therapy data were extracted from medical records while post-treatment immuno-hematological measurements were done on blood samples collected at the time of enrollment. Results: The prevalence of anemia, leukopenia, and thrombocytopenia before initiation of antiretroviral treatment was higher, although anemia and thrombocytopenia decreased correspondingly after initiation of treatment leukopenia increased by 4%. Mean values of immuno-hematological parameters before and after treatment initiation were significant ( p  < 0.05). CD4+ T-cell count <200 cells/µL was the only independent risk factor for anemia and leukopenia before highly active antiretroviral therapy, while stage IV disease, female sex, zidovudine, lamivudine, and nevirapine treatment, and intestinal parasite infection were predictors of anemia after treatment initiation. Conclusion: The study revealed that hematological abnormalities are common in HIV infection, while the occurrence of abnormalities after highly active antiretroviral therapy initiation. Different risk factors are associated with hematological abnormalities at pre- and post-highly active antiretroviral therapy with regular monitoring of risk factors, adherence to the early initiation of highly active antiretroviral therapy, and conduct of further longitudinal studies are recommended.